Smart transport company / Tyson Bayak Tubang Oleah...[et al.] - Oleah, Bayak Tubang; Yusup, Hajizah; Samuel, Henrita; Doson, Sylester Birai (2010)
After closing extensive research on the business opportunity available in Kota Samarahan District Council area, we decided to specify our business in providing transport for oil palm plantation. We have come out with a partnership business which consists of five members and the name of our company is Smart Transport Enterprise Each partner contributes certain amounts of cash as agreed in our agreement. Our main business activity is to carry Fresh Fruit Bunch (FFB) from oil palm plantations in Kota Samarahan, Asajaya and Serian to Kilang Sawit FELCRA Berhad Samarahan. Our business will be operating at Pusat Incubator dan Bimbingan Usahawan (PIBU) Kota Samarahan, Lot 7993 (E&F) Blok 9, Tingkat 1 Muara Tuang Land District, Jalan Dato Mohd Musa, 94300 Kota Samarahan. All partners are entitled to participate in the business management. We have agreed that Mr. Tyson Bayak Tubang Oleahl is the General Manager, Marketing Manager : M Mr. Basil Linang, Financial Manager : Mr. Sylester Birai ak Michael Doson, and Administration Manager : Miss Hajizah bt Yusup. The management will be lead by General Manager and assisted by other managers. The general manager is responsible in controlling, leading, organizing, and planning the entire business. Administration Manager is responsible for the entire jobs related to office administration. The marketing Manager is responsible in preparing marketing plan. This includes identifying the target market share, develop sales forecast and develop the marketing strategies, the operation of our business is controlled and monitored by Operation Manager. The financial Manager will take responsibility in preparing budget and financial statement for each department expenses.